The Narrative Strategy of MS Glow for Men in Campaigning the (Un- to) Glowing Men on YouTube - Atiek Puji Lestari; Hendra Agustian; Annisa Laila Alvi Syahri; Andyka Pratiwi4; Elsa EMaghfira (Jobmark: Journal of Branding and Marketing Communication, 2025)
The rapid growth in the use of social media as a marketing tool, mainly through video advertising on YouTube, indicates a significant shift in marketing strategies. This study analyzes the MS Glow for Men advertisement on YouTube, endorsed by Marshel Widianto and Babe Cabita, using an instrumental approach based on the theory and method of Branded Content Analysis (BCA). The advertisement promotes a different representation of masculinity, featuring men with positive personalities and standard bodies, contrasting with the typical image of athletic men in male grooming product advertisements. This approach highlights how influencers influence audiences through various textual, technical, and kinesthetic modes. The results reveal that the advertisement successfully alters the audience's perception of masculinity, convincing them that masculinity is not only related to physical attributes but also personality and character. The positive response from the social media audience signifies the advertisement's success in representing a new concept of masculinity. This study contributes theoretically by demonstrating the effectiveness of the instrumental approach in analyzing representations of masculinity. Practically, the new approach in advertising creativities provides opportunities to promote a more inclusive and diverse concept of masculinity in the marketing domain.